Plant intraspecific variation modulates nutrient cycling through its below ground rhizospheric microbiome. (29th May 2019) - Pérez‐Izquierdo, Leticia; Zabal‐Aguirre, Mario; González‐Martínez, Santiago C.; Buée, Marc; Verdú, Miguel; Rincón, Ana; Goberna, Marta
Abstract: Plant genetic variation, through its phenotypic display, can determine the composition of below ground microbial communities. Variation within a species is increasingly acknowledged to have substantial ecological consequences, particularly through trophic cascades. We hypothesized that the intraspecific genotypic variation of the tree host might impact the phylogenetic composition of its rhizospheric microbial communities, by favouring particular clades, that might be further reflected in ecosystem process rates. We tested whether the intraspecific genotypic variation of Pinus pinaster modulates nutrient cycling by determining the phylogenetic structure of its symbiotic ectomycorrhizal fungi and rhizospheric bacteria. We sequenced fungal and bacterial molecular markers and reconstructed phylogenies in the rhizosphere of P. pinaster trees belonging to three genotypic variants (Mediterranean, Atlantic, African) in three 45‐year‐old common garden experiments, and measured seven soil enzymatic activities. Local effects, based on differences in elevation and soil conditions across sites, were strong predictors of the ectomycorrhizal and bacterial communities thriving in tree's rhizosphere. Across‐site variation also explained differences in phosphorus cycling. We detected, however, a significant effect of the plant genotype on the phylogenetic structure of the root‐associated microbiota that was consistent across sites. The most productive Mediterranean plant genotype sheltered the most distinct root microbiome, with the dominant Basidiomycetes and Proteobacteria having a strong influence on the phylogenetic microbial community structure and associating with an enhanced hydrolysis of celluloses, hemicelluloses and chitin. Beneath the less productive Atlantic genotype, the less abundant Ascomycetes and up to thirteen bacterial phyla shaped the phylogenetic microbial structure, and predicted the rates of peptidase. Ectomycorrhizal fungi explained the activity of cellulases and protease, and bacteria that of hemicellulases and chitinase, suggesting functional complementarity. Synthesis. This is the first report using three‐replicated long‐term common gardens in mature forests to disentangle plant genotype‐ and site‐specific drivers of the rhizospheric microbiome and its enzymatic potential. We concluded that intraspecific variation in primary producers leaves a phylogenetic signature in mutualists and decomposers that further modulate key steps in carbon and nitrogen cycles. These results emphasize the ecological relevance of plant intraspecific diversity in determining essential plant–soil feedbacks that control ecosystem productivity and performance. Abstract : This is the first report using three‐replicated long‐term common gardens in mature forests to disentangle plant genotype‐ and site‐specific drivers of the rhizospheric microbiome and its enzymatic potential. We concluded that intraspecific variation in primary producers leaves a phylogenetic signature in mutualists and decomposers that further modulate key steps in carbon and nitrogen cycles. These results emphasize the ecological relevance of plant intraspecific diversity in determining essential plant–soil feedbacks that control ecosystem productivity and performance.